Migratory birds: Silent panic and play – Reflections on memories of childhood and adolescence from World War II - Stenvold, Heidi; Fause, Åshild (Nordlit, 2015)
The museum of reconstruction for Finnmark and Northern Troms uses personal war memories from childhood and adolescence e.g. in exhibitions, articles and lectures. However, 70-year-old memories are most likely processed and changed over time, and critics often consider memories untrustworthy. Some scholars claim that positive memories stick better than negative memories, while others vice versa. The first research question addresses this problem by asking: “Are good or bad experiences most likely remembered?”. Discussing this revealed different factors affecting the memories, such as the desire to honor the parents, the questionnaire design, and more. The purpose of the second research question was to gain a deeper understanding of the factors that might would enhance or hinder resilience or vulnerability in the face of their war experiences at the time.